Parathyroid Hormone as a Predictor of Post-Thyroidectomy Hipocalcemia: A Prospective Evaluation of 100 Patients - Melo, F (2015)
INTRODUCTION: Hypocalcemia is a frequent complication after total thyroidectomy and the main reason for prolonged hospitalization of these patients. MATERIAL AND METHODS: We studied prospectively 112 patients who underwent total or completation thyroidectomy between June 2012 and November 2013. Twelve patients with preoperative changes in parathyroid function were excluded. Parathyroid hormone and calcium levels were determined pre-operatively, immediately after surgery, on 1st day and on 14th day after surgery. RESULTS: Of the 100 patients enrolled, 60 have developed hypocalcaemia (60%) but only 14 patients had symptomatic hypocalcaemia. It mostly occurs 24 hours after surgery (76.7%). It was permanent in 3 patients and temporary in the others. In the 60 patients with hypocalcaemia, it has been found hypoparathyroidism in 19 patients immediately after surgery, in 14 patients on 1st day but only 3 had hypoparathyroidism (patients with permanent hypocalcaemia). Comparing the group of patients with and without hypocalcaemia we found a decrease of parathyroid hormone in both (immediately after surgery and on 1st day) but was more important in the hypocalcaemia group (p = 0.004 and p < 0.001). The decrease of PTH levels was more pronounced in the hypocalcaemia group, with significance on the first day (22.29% vs 50.29%, p < 0.001). The best predictor of hypocalcaemia identified was the decrease of parathyroid hormone levels > 19.4% determined on the 1st day (sensitivity = 82%; specificity = 63%). DISCUSSION: In our study there was a high incidence of hypocalcemia (60%), expressed predominantly 24 hours after surgery and conditioned, in these patients, a longer hospital stay. However, only 3 patients (3%) had permanent hypocalcemia. We still found a match in the oscillation of serum calcium levels and parathyroid hormone which identified the decrease in parathyroid hormone on the first day after surgery as a reliable predictor of hypocalcemia. CONCLUSION: Decrease of parathyroid hormone levels > 19.4% determined on 1st day is a good predictor of hypocalcemia after total / completation thyroidectomy, allowing to identify patients at higher risk of hypocalcemia, medicate them prophylactically and get early and safe discharges.